2018
DOI: 10.1159/000486130
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rate without Brain Abnormalities on Postnatal Ultrasonography among Monochorionic Twins after Fetoscopic Laser Photocoagulation for Selective Intrauterine Growth Restriction with Concomitant Oligohydramnios

Abstract: Introduction: We aimed to clarify the survival rate without brain abnormalities (BA) after fetoscopic laser photoco­agulation (FLP) for monochorionic diamniotic twin gestations (MCDA) with selective intrauterine growth restriction (sIUGR) accompanied by abnormal umbilical artery (UA) Doppler waveforms and isolated oligohydramnios in the sIUGR twin. Materials and Methods: This retrospective study included 52 cases that underwent FLP. The main outcome was survival rate without BA of the twins at age 28 days. BA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Fetoscopic laser surgery is one option for managing severe selective FGR . Ishii et al reported that conservative observational management resulted in unfavorable outcomes if the smaller fetus had both oligohydramnios and abnormal UA Doppler waveforms.…”
Section: Discussionmentioning
confidence: 99%
“…Fetoscopic laser surgery is one option for managing severe selective FGR . Ishii et al reported that conservative observational management resulted in unfavorable outcomes if the smaller fetus had both oligohydramnios and abnormal UA Doppler waveforms.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse outcome was defined as the occurrence of IUFD. The definitions of TTTS, sIUGR, and TAPS are described in the Appendix (Tables ) as per the International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) practice guidelines . Discordant ratio of birth weight (DRBW) was defined with two live births, calculated using the following formula: ([larger BW−smaller BW]/larger BW) × 100% as described by Hartley et al The prevalence of DRBW more than 25% (BWD 25%) was confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown the application of FLS for sIUGR with absent or reverse end-diastolic velocity (AREDV) in the umbilical artery (UA) [30][31][32]. FLS may be a promising treatment option for sIUGR when accompanied by both AREDV in UA and severe oligohydramnios of IUGR twins [33,34]. Oligohydramnios in the IUGR twin may be an essential indication for FLP for sIUGR.…”
Section: Fetoscopic Laser Surgerymentioning
confidence: 99%